The Relationship of Addictive-Like Eating, Relationship Quality, Body Satisfaction, Personality Tendencies, and Hedonistic Eating - Kaya, Sena; Kumova, Filiz (Beykoz Üniversitesi, 2024)
The present study aimed to explore the correlational and predictive relationships between addictive-like eating tendencies and hedonistic eating, body satisfaction, romantic relationship quality, and obsessivecompulsive, borderline, and dependent personality disorder tendencies. Possible differentiation in addictive-like eating tendencies by gender and marital status were also analyzed for explanatory purposes. Furthermore, the addictive-like eating and hedonistic eating tendencies of the participants were compared concerning their body mass index. Seven hundred sixty-eight participants aged 18-63 participated in the present study. The results revealed that there were medium positive correlations between addictive-like eating and hedonistic eating, obsessive-compulsive, borderline, and dependent personality disorder tendencies, whereas there was a medium correlation between addictive-like eating and body satisfaction. Furthermore, hedonistic eating, body satisfaction, and borderline personality disorder tendencies were found to be significant predictors of addictive-like eating inclination. It was found that these predictive relationships did not differ by gender or marital status. Moreover, results indicated that both addictive-like eating and hedonistic eating behaviors of the participants whose body mass indexes were equal to or above 25 were significantly higher than those with body mass indexes lower than 25. Based on the results of the present study, it was suggested that the evaluation of individuals exhibiting addictive-like eating behaviors in terms of deterioration in body satisfaction, hedonistic eating tendency, and DPD, OCPD, but especially potential BPD dispositions, would help the clinicians following a comprehensive treatment plan and sustaining more efficiency concerning the psychotherapy processes and outcomes. Moreover, it was recommended to replicate the present study with the participation of a patient group with extremely addictive-like behaviors, as the results might differ depending on the sample.

Mevcut çalışma bağımlılık benzeri yemenin algılanan romantik ilişki kalitesi, beden memnuniyeti, hedonistik yeme ve obsesif-kompülsif, sınır durum ve bağımlı kişilik bozukluğu eğilimleri ile olan ilişkisinin korelasyonal ve yordayıcı ilişkisini araştırmayı amaçlamaktadır. Bağımlılık benzeri yeme eğiliminin cinsiyet ve medeni duruma göre olası farklılaşmaları da uygun analizlerle incelenmiştir. Ayrıca katılımcıların bağımlılık benzeri yeme ve hedonistik yeme eğilimleri vücut kitle indekslerine göre de karşılaştırılmıştır. Bu çalışma 18-63 yaş arasındaki 768 katılımcıyla gerçekleştirilmiştir. Sonuçlar bağımlılık benzeri yeme eğilimi ile hedonistik yeme, Obsesif-Kompulsif, Borderline ve Bağımlı kişilik bozukluğu eğilimleri arasında orta düzey pozitif, bağımlılık benzeri yeme ile beden memnuniyeti arasında ise orta düzey negatif korelasyon olduğunu göstermiştir. Ayrıca hedonistik yeme, beden memnuniyeti ve Sınır-Durum Kişilik Bozukluğu eğiliminin, bağımlılık benzeri yeme eğiliminin anlamlı yordayıcıları olduğu görülmektedir. Bu yordayıcı ilişkilerin cinsiyete veya medeni duruma göre farklılık göstermediği bulunmuştur. Ayrıca analizler sonucunda vücut kütle indeksi 25 ve üzerinde olan katılımcıların hem bağımlılık benzeri yeme hem de hedonistik yeme davranışlarının, vücut kütle indeksi 25’ten düşük olan katılımcılara göre anlamlı derecede yüksek olduğu tespit edilmiştir. Bu çalışma sonuçlarına dayanarak, bağımlılık benzeri yeme davranışı sergileyen bireylerin beden memnuniyetinde bozulma, hedonistik yeme eğilimi, Bağımlı Kişilik Bozukluğu, Obsesif Kompülsif Kişilik Bozukluğu ve özellikle de Borderline Kişilik Bozukluğu eğilimleri açısından değerlendirilmesinin, klinisyenlere kapsamlı bir tedavi planı takip edilmesi ve psikoterapi sürecinin veriminin arttırılması açısından faydalı olacağı öngörülmüştür. Bunun yanı sıra, sonuçların örnekleme göre farklılık gösterebileceği göz önünde bulundurularak, bu çalışmanın aşırı düzeyde bağımlılık benzeri yeme davranışı gösteren bir hasta grubu ile de tekrarlanması önerilmiştir.
Bağımlılık Benzeri Yemenin, İlişki Kalitesi, Beden Memnuniyeti, Kişilik Eğilimleri, Hedonistik Yemeyle İlişkisi
Keywords: Addictive-Like Eating; Hedonistic Eating; Romantic Relationship Quality; Body Satisfaction; Personality Disorder Tendencies; Bağımlılık Benzeri Yeme; Romantik İlişki Kalitesi; Hedonistik Yeme; Beden Memnuniyeti; Kişilik Bozukluğu Eğilimleri